Prevalence and Antibiotic Resistance Patterns of Uropathogens in Patients with Urinary Tract Infections - Omar Hussam Jumaah; Abeer Mansour Abdel Rasool; Lina Abbas Naser (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Urinary tract infections (UTIs) remain a significant global health concern, frequently complicated by the rise of antimicrobial resistance (AMR) among common uropathogens. Specific Background: In Iraq, increasing rates of multidrug-resistant bacterial strains, particularly Escherichia coli and Klebsiella pneumoniae, have limited therapeutic options and complicated clinical management. Knowledge Gap: Despite numerous studies on global AMR, region-specific data on uropathogen prevalence and susceptibility profiles in northern Iraq remain scarce. Aims: This study aimed to determine the prevalence and antibiotic resistance patterns of bacterial isolates from UTI patients in Mosul, Iraq, to guide empirical treatment and inform antimicrobial stewardship. Results: Among 173 isolates, E. coli (34.7%), K. pneumoniae (23.1%), and Pseudomonas aeruginosa (17.3%) were predominant. The highest susceptibility was observed with Meropenem (95.4%) and Imipenem (92.5%), while Ciprofloxacin resistance reached 42.2%, indicating restricted treatment options. Novelty: The study provides the most recent regional data on uropathogen distribution and resistance trends in Mosul, integrating microbiological surveillance with demographic analysis. Implications: These findings underscore the urgent need for continuous resistance monitoring, rational antibiotic use, and local antimicrobial stewardship programs to curb the spread of resistant uropathogens and improve clinical outcomes.Highlight : E. coli remains the leading uropathogen in UTIs, followed by K. pneumoniae and P. aeruginosa. High resistance to Ciprofloxacin (42.2%) indicates limited treatment options. Regular surveillance of antibiotic resistance is essential for effective therapy and control. Keywords : Urinary Tract Infection (UTI), Uropathogens, Antibiotic Resistance, Prevalence, Antimicrobial Susceptibility